Pengaruh Performance Expectancy dan Effort Expectancy terhadap HRA Adoption Behaviour dengan Mediasi HRA Adoption Intention pada Karyawan PT Nikomas Gemilang dan PT Pou Chen di Kabupaten Serang - Nika Arini; Tiarapuspa Tiarapuspa; Sarfilianty Anggiani; Beta Oki Baliartati; Jayida Syarifah (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the effect of performance expectancy and effort expectancy on HRA adoption behavior mediated by HRA adoption intention. The sample for this study used non probability sampling with purposive sampling techniques involving 245 respondents who were employees of PT Nikomas Gemilang and PT Pou Chen in Serang district who filled out a questionnaire via Google Form. The analysis method used was SEM (Structural Equation Modeling) using AMOS version 23. The instrument tests used in this study were validity tests, reliability tests, and goodness of fit tests. The results of the study indicate that there is an influence between Performance Expectancy and Effort Expectancy on HRA Adoption Behavior, mediated by HRA Adoption Intention. The managerial implications of the results of this study are expected to assist organizations in improving or encouraging more initiatives for the digitization of work services in the manufacturing sector, so that companies become more adaptive to technology-based innovations.